(3cJGH GdRcGIs - (3eMeO Hf YHO Gddg Hf jMji Hf GdLO GdagQj,J (B586 (3g` s
(3ChdgG (B:s
(3bGd Gdabjg CHh HcQ eMeO Hf YHO dGdg Hf jMji Hf GdLO GdagQi GdcdGe ai gPG GdecJhH jTJed Ydi YTQI aUhd ef CMcGe GdRcGI s
(3BNQgG (B:s
(3hCe GdbSe GdKGef bJYWi RcGI GdaWQ hJbSe HGdGLJgGO ced GdLRA HMeO Gddg JYGdi s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs